8m-(-3)+5(m+3)=

Simple and best practice solution for 8m-(-3)+5(m+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8m-(-3)+5(m+3)= equation:


Simplifying
8m + -1(-3) + 5(m + 3) = 0

Multiply -1 * -3
8m + 3 + 5(m + 3) = 0

Reorder the terms:
8m + 3 + 5(3 + m) = 0
8m + 3 + (3 * 5 + m * 5) = 0
8m + 3 + (15 + 5m) = 0

Reorder the terms:
3 + 15 + 8m + 5m = 0

Combine like terms: 3 + 15 = 18
18 + 8m + 5m = 0

Combine like terms: 8m + 5m = 13m
18 + 13m = 0

Solving
18 + 13m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 13m = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 13m = 0 + -18
13m = 0 + -18

Combine like terms: 0 + -18 = -18
13m = -18

Divide each side by '13'.
m = -1.384615385

Simplifying
m = -1.384615385

See similar equations:

| -9b+27=72 | | 3x+8+2x-5=23 | | 22=(b+3) | | x^2-3x-y=0 | | -2(b-9)=2 | | 12x+3=6x-15 | | 7x^2-y^2=31 | | 20x^4-12x^2=0 | | (x-6)(x-4)=-1 | | 17+x=18 | | 3x+9=3x+13 | | -4y-10=7y+12 | | 0.007(x+3)=0.008x+0.018 | | -2(4g+9)+6(-6g-9)= | | (2x+1)9+5(5x+3)= | | 11=0.333a+2 | | -2(x+6)-8=-20 | | 7y-11=6(2y+3)-5y | | 11=.0333a+2 | | 6[5y-(3y-1)]=4(3y-7) | | 450=-45+b | | .5b+4=.125b+86 | | 7+4x=8x-6 | | 20r-19r=3 | | 10Q=.01 | | 20t-19r=3 | | 7.6r-1=1.6r | | 7/5=d/10-3d/2 | | 1-k+2k=11+5k | | 18.13-3.18c=6.32c-8.32 | | 6x-10=4x+8 | | -14g-5b-8g+9+3b= |

Equations solver categories